Efeito do período de jejum na fase final de criação de frangos de corte machos sobre desempenho e mortalidade - Sartori, José Roberto [UNESP]; Gonzales, Elisabeth [UNESP]; Mendonça de Souza, Eduardo; Mendes, Ariel Antonio [UNESP]; Wechsler, Francisco Stefano [UNESP] (My University, 1997)
The objective of this work was to evaluate effect of fasting period in the last growing phase on performance and mortality of male broilers. Two thousand one-day old male chicks were distributed in five randomized blocks according to a 4x2 factorial. (Four feeding programs (FP): ad libitum or one of three fasting schedules: 8-12, 12-16 and 8-16; and two strains (S): Ross or Hubbard-Peterson). Fifty birds were used per replicate. Birds were raised under identical feed and management conditions until day 42. During the experimental period (days 43-56), average temperature, relative humidity and temperature-humidity index (THI) recorded at day and at night were 29.4°C, 57.7 % and 78.1; and 22.0°C, 73.1% and 67.4, respectively. No SxP interaction was observed for all characteristics studied. At day 56, the Ross broilers showed higher mean weight (3104 g), weight gain, WG (3059 g), feed/ gain ratio, FC (2.22) and production factor, PF (213), than the Hubbard-Peterson birds (3011, 2967, 2.28 and 194, respectively). During the experimental period, the Ross broilers showed higher WG (831 g) and FC (3.40) than the Hubbard-Peterson ones (770 and 3.67, respectively). Birds submitted to the 8-12 h fast showed higher feed intake (2864 g) than those that fasted during the 8-16 period (2690). No effect of P on mortality was observed, either considering the overall period (days 1-56) or the experimental period (days 43-56). Fasting in the last phase of rearing not aided by other practices failed to decrease heat stress effects on performance and mortality of male broilers.
The effect of fasting period in the last phase of rearing on performance and mortality of male broilers
Keywords: Broilers; Fasting; Heat stress; Mortality; Performance